COMPARISON OF PLAIN X-RAY WITH MRI IN PATIENTS OF RHEUMATOID ARTHRITIS AND SERONEGATIVE ARTHRITIS - yadav, bhagwan; Puri, Sulabh; Mathur, Manoj (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of this study was to compare the findings of plain X-ray with magnetic resonance imaging (MRI) in patients of rheumatoid arthritis and seronegative arthritis. Methods: A total of 35 patients who apparently fulfilled the clinical diagnostic criteria were included on the basis of serological tests for seropositive and seronegative arthritis. After fulfillment of all the inclusion and exclusion criteria, radiographic images and MRI of joints were done by various MR techniques. Findings of plain radiography and MRI in various cases were compiled and subjected to statistical analysis using IBM software SPSS v20. Results: Twenty-one patients were diagnosed with seropositive arthritis and 14 were with seronegative arthritis. The findings showed that MRI was 100 accurate in diagnosing seropositive and seronegative arthritis while the accuracy of X-ray in detecting seropositive arthritis (in comparison to MRI) was 62.86% with sensitivity of 38.1%, specificity of 100%, positive predictive value (PPV) of 100%, and negative predictive value (NPV) of 51.85%. The accuracy of X-ray in detecting seronegative arthritis (in comparison to MRI) was 85.71% with a sensitivity of 64.29%, specificity of 100%, PPV of 100%, and NPV of 80.77%. Conclusion: MRI of seropositive and seronegative arthritis is a highly rewarding investigation and should be undertaken in all cases where plain radiographs are positive and when there is clinical suspicion of a disease but the X-ray films are not diagnostic.